2020
DOI: 10.1016/s2352-3018(20)30189-2
|View full text |Cite
|
Sign up to set email alerts
|

Simplified dolutegravir dosing for children with HIV weighing 20 kg or more: pharmacokinetic and safety substudies of the multicentre, randomised ODYSSEY trial

Abstract: Summary Background Paediatric dolutegravir doses approved by stringent regulatory authorities (SRAs) for children weighing 20 kg to less than 40 kg until recently required 25 mg and 10 mg film-coated tablets. These tablets are not readily available in low-resource settings where the burden of HIV is highest. We did nested pharmacokinetic substudies in patients enrolled in the ODYSSEY-trial to evaluate simplified dosing in children with HIV. Methods We did p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 17 publications
1
33
2
Order By: Relevance
“…Pharmacokinetics sub‐studies of the randomized ODYSSEY trial recently suggested that adult dolutegravir 50 mg film‐coated tablets given once daily provide appropriate pharmacokinetic profiles in children weighing ≥ 20 kg [15]. In our retrospective study, where subjects initiated dolutegravir before the revision of dolutegravir paediatric dosing guidelines, low dolutegravir plasma levels may have contributed to VF in some patients weighing 20–30 kg (and receiving 25 mg dolutegravir once daily).…”
Section: Discussionmentioning
confidence: 90%
“…Pharmacokinetics sub‐studies of the randomized ODYSSEY trial recently suggested that adult dolutegravir 50 mg film‐coated tablets given once daily provide appropriate pharmacokinetic profiles in children weighing ≥ 20 kg [15]. In our retrospective study, where subjects initiated dolutegravir before the revision of dolutegravir paediatric dosing guidelines, low dolutegravir plasma levels may have contributed to VF in some patients weighing 20–30 kg (and receiving 25 mg dolutegravir once daily).…”
Section: Discussionmentioning
confidence: 90%
“…Results of other nested pharmacokinetic substudies are reported elsewhere. 5,6 In the first substudy, we enrolled children weighing 14 kg to less than 20 kg. Following a review of results, we did a second substudy in this weight band, using a different dolutegravir formulation and dose.…”
Section: Odyssey (Nct02259127mentioning
confidence: 99%
“…3 The more recently introduced integrase inhibitor, dolutegravir, has the potential to change the use of ART for children; in adults and older children, dolutegravir has high virological efficacy, good tolerability, minimal drug-drug interactions, and a high barrier to resistance. 4 , 5 These characteristics combined with a low effective dose and, consequently, low manufacturing costs and small formulation size have made dolutegravir a preferred treatment option for most countries regardless of income status.…”
Section: Introductionmentioning
confidence: 99%
“…Further pharmacokinetic evaluation conducted as a substudy of the Odyssey trial evaluated the use of the 50 mg tablet in children between 20 kg and 30 kg. 11 Acceptable pharmacokinetics and side-effect profile supported the USFDA registration of DTG 50 mg daily in children from 20 kg. In addition, the new dosage recommendation was added to the WHO and several national guidelines, including the South African national ART guidelines.…”
Section: Dolutegravirmentioning
confidence: 87%